Introduction to the Special Section "Proxy Records and Mechanistic Studies of the Late Quaternary Paleoceanography of the Western Pacific Marginal Seas Using IMAGES Cores" - Meixun Zhao; Min-Te Chen; Luc Beaufort (Terrestrial, Atmospheric and Oceanic Sciences, 2008)

(untitled)
The western Pacific Ocean plays an important role in regulating and modulating the global climate system on interannual to geological timescales. Excellent records have been acquired by coring high sedimentation rate sites in the marginal seas of the western Pacific Ocean during IMAGES cruises. This special section has been proposed to publish papers presenting high-resolution records and the interpretation of climate changemechanisms revealed by these records.